1998
DOI: 10.1001/archpsyc.55.8.702
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Social Rhythm Disruption in the Onset of Manic and Depressive Bipolar Episodes

Abstract: Background:The association between stressful life events and onset of bipolar episodes is unclear. The association between bipolar episode onset and types of life events that disrupt social routines, and potentially sleep, has not yet been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
2
7

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(206 citation statements)
references
References 42 publications
10
186
2
7
Order By: Relevance
“…For example, Hunt, Bruce-Jones, and Silverstone (1992) found an approximate fourfold elevation in the rates of severe life events in the month before relapse compared to other months among patients with bipolar disorder. Malkoff-Schwartz et al (1998) found an approximate twofold increase in severe life events in the 8 weeks preceding an episode compared to a control period. One study failed to find an increase in life events in the 3 months before episodes (McPherson, Herbison, & Romans, 1993).…”
Section: Studies That Do Not Distinguish Polarity Of Symptomsmentioning
confidence: 81%
See 3 more Smart Citations
“…For example, Hunt, Bruce-Jones, and Silverstone (1992) found an approximate fourfold elevation in the rates of severe life events in the month before relapse compared to other months among patients with bipolar disorder. Malkoff-Schwartz et al (1998) found an approximate twofold increase in severe life events in the 8 weeks preceding an episode compared to a control period. One study failed to find an increase in life events in the 3 months before episodes (McPherson, Herbison, & Romans, 1993).…”
Section: Studies That Do Not Distinguish Polarity Of Symptomsmentioning
confidence: 81%
“…Not surprisingly, then, investigators also have examined negative life events and bipolar depression. Although researchers have considered other types of life events, no support has been obtained for schedule-disrupting life events (Malkoff-Schwartz et al, 1998 nor goal attainment life events as triggers of depression (Johnson et al, 2000;Johnson, Kizer, Ruggero, Goodnick, & Miller, 2004). The focus of this section, then, is on negative life events and depression.…”
Section: Life Events and Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Akiskal (1996) has suggested that the behavior of the hyperthymic temperament may bring about situations that trigger manic episodes. For example, the excessively driven, workaholic lifestyle may promote sleep deprivation, a common trigger for mania (Wehr, 1991;Malkoff-Schwartz et al, 1998). In short, achievement striving may be part of a pathway that intensifies risk for manic symptoms.…”
Section: Discussionmentioning
confidence: 99%